Perspectives on Canadian Economic Development: Class, Staples, Gender, and Elites - Laxer, Gordon D. (Oxford University Press, 1991)
This new collection of readings brings together articles offering a wide range of perspectives on the pattern of Canada's economic development. Among the features they emphasize are Canada's historical reliance on resource (staple) exportation; trade dependence on one or two metropolitan centres; regional economic disparities,; a tendency towards centralized control of economic institutions; and a high-wage labour force. Organized in five sections - neoclassical economics, the staples approach, elites, class politics, and the roles of gender and labour in economic development - the selections in this book reflect the variety of approaches to Canada's economic history that have developed over the last quarter century. –Publisher's description
OCLC: 23053001
Keywords: Canada; Canada Conditions économiques; Canada Economic conditions; Canada Economic conditions 1971-1991; Economic history; Kanada; Wirtschaftsentwicklung